2013
DOI: 10.1371/journal.pone.0069913
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cytochrome P450 Reductase Enhances Long-Term Hematopoietic Stem Cell Repopulation Efficiency in Mice

Abstract: BackgroundBone marrow microenvironment (niche) plays essential roles in the fate of hematopoietic stem cells (HSCs). Intracellular and extracellular redox metabolic microenvironment is one of the critical factors for the maintenance of the niche. Cytochrome P450 reductase (CPR) is an obligate electron donor to all microsomal cytochrome P450 enzymes (P450 or CYP), and contributes to the redox metabolic process. However, its role in maintaining HSCs is unknown.ObjectiveTo examine the effects of low CPR expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For EEFs this association is obvious with parasite residency within the hepatocyte; for gametocytes this is less obvious as circulating gametocytes are rarely in juxtaposition to a potential source of metabolism. However, P. vivax and P. falciparum gametocytes, including mature stages 20,21 , are sequestered/enriched in the bone marrow 22,23 , which is also endowed with significant P450-dependent metabolic capacity 24–26 . To address this possibility, the ability of PQ and OH-PQm to generate H 2 O 2 in mouse bone marrow cell extracts was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…For EEFs this association is obvious with parasite residency within the hepatocyte; for gametocytes this is less obvious as circulating gametocytes are rarely in juxtaposition to a potential source of metabolism. However, P. vivax and P. falciparum gametocytes, including mature stages 20,21 , are sequestered/enriched in the bone marrow 22,23 , which is also endowed with significant P450-dependent metabolic capacity 24–26 . To address this possibility, the ability of PQ and OH-PQm to generate H 2 O 2 in mouse bone marrow cell extracts was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Generation of ROS was determined by two methods: fluorometric analysis and microscopic fluorescence imaging, using 2,7-dichlorofluorescin diacetate (DCFH-DA) as described by our previous method [16] . DCFH-DA was a cell-permeable probe, and was widely used to detect the ROS generation [39] [41] . For fluorometric analysis, cells (1×10 6 cells/well) were seeded in 60 mm dish.…”
Section: Methodsmentioning
confidence: 99%
“…The latter studies revealed that attenuated P450 reductase expression enhanced the repopulation efficiency of hematopoietic stem cells (Zhang et al, 2013b). However, elucidating the molecular mechanisms behind this effect would be difficult because the loss of the P450 reductase would be expected to dramatically reduce all P450 activity.…”
Section: H Stem Cellsmentioning
confidence: 99%